SERVICE PERIOD AS A MODERATOR TO THE BEHAVIOUR AND WORK PERFORMANCE RELATIONSHIP IN THE ORGANISATION - Khatijah Othman,; Siti Nurbaya Ismail,; Shahrul Hafifi Mohd Fuad,; Masni Md Hasim,; Fadhilah Othman,; Muhammad Rahmat Abdullah,; Norwini Zaidi,; Nur Adlina Addenan,; Nik Nadian Nisa Nik Nazli, (Asian Academy of Management Journal, 2019)
Performance and productivity are strongly influenced by the workers’ behavioural attitudes. Committed employees’ behaviours will produce higher performance and productivity in their work. Undeniably, the better commitment would help to reduce employees’ personal problems such as differing work, absenteeism, and negligence in doing work. High performance affects employees and ensures that every task is done efficiently, and it provides employees a high level of job satisfaction. The longer the worker stays in a workplace, the higher the performance level shown towards the organisation. The objective of this study is to examine the relationship between the workers’ behaviours and work performances in the organisation, and to determine the service period as a moderator in relationship between behaviour and work performance. The method used in this study is a quantitative methodology, and the survey questionnaires have been conducted on 100 respondents consisting of professional and administrative officers in an organisation. The data analysis was performed using Structural Equation Modeling (SEM) method with the help of AMOS software version 23. The finding shows that there is a positive relationship between employees’ behaviour and work performance, and the duration of service moderated the relationship between behaviour and work performance. In this regard, workers who have worked a long period of service with an organisation exhibit the behaviour of commitments to work and produce more efficient and effective work performance in the organisation.